Electrochemical Monitoring of the Early Events of Hydrogen Peroxide Production by Mitochondria1. Issue 26 (22nd May 2014) - Suraniti, Emmanuel; Ben‐Amor, Salem; Landry, Pauline; Rigoulet, Michel; Fontaine, Eric; Bottari, Serge; Devin, Anne; Sojic, Neso; Mano, Nicolas; Arbault, Stéphane
Abstract Mitochondria consume oxygen in the respiratory chain and convert redox energy into ATP. As a side process, they produce reactive oxygen species (ROS), whose physiological activities are still not understood. However, current analytical methods cannot be used to monitor mitochondrial ROS quantitatively and unambiguously. We have developed electrochemical biosensors based on peroxidase‐redox polymer‐modified electrodes, providing selective detection of H2O2 with nanomolar sensitivity, linear response over five concentration decades, and fast response time. The release of H2O2 by mitochondria was then monitored under phosphorylating or inhibited respiration conditions. We report the detection of two concomitant regimes of H2O2 release: large fluxes (hundreds of nM) under complex III inhibition, and bursts of a few nM immediately following mitochondria activation. These unprecedented bursts of H2O2 are assigned to the role of mitochondria as the hub of redox signaling in cells.